The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.bjane.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Pain after sternotomy – review

Abstract: Heart surgery is performed mainly via medium sternotomy, which results in significant postoperative pain and a non-negligible incidence of chronic pain. Effective pain control improves patient satisfaction and clinical outcomes. There is no clearly superior technique. It is believed that a combined multimodal analgesic regimen (using different techniques) is the best approach for treating postoperative pain, maximizing analgesia and reducing side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 51 publications
2
74
2
5
Order By: Relevance
“…The causes of these reductions may be related to surgical manipulation, degree of sedation, cardioplegic agents, thermal damage, and cardiopulmonary bypass used that lead to change in pulmonary mechanics and respiratory compliance (3,(18)(19)(20)(21). Also, post-operative pain may cause of immobilizing and restrictive pulmonary pattern (22). However, the pain scales in this study showed no difference between admission and discharge periods.…”
Section: Discussioncontrasting
confidence: 63%
“…The causes of these reductions may be related to surgical manipulation, degree of sedation, cardioplegic agents, thermal damage, and cardiopulmonary bypass used that lead to change in pulmonary mechanics and respiratory compliance (3,(18)(19)(20)(21). Also, post-operative pain may cause of immobilizing and restrictive pulmonary pattern (22). However, the pain scales in this study showed no difference between admission and discharge periods.…”
Section: Discussioncontrasting
confidence: 63%
“…43 Moreover, better control of acute pain after cardiac surgery has been shown to reduce cardiovascular morbidity, pneumonia, and hypercoagulability due to reductions in the stress response. [44][45][46] …”
Section: Acute Pain Severity and Treatmentmentioning
confidence: 99%
“…Ağrı kontrolünde herhangi bir tekniğin üstünlüğü saptanamamıştır. Kombine multimodal analjezi ağrı yönetimini sağlayarak, komplikasyonlar ve yan etkiler azaltılabilir 65,66 .…”
Section: Ağrıunclassified